Mucoadhesion: A food perspective. (November 2017) - Cook, Sarah L.; Bull, Stephanie P.; Methven, Lisa; Parker, Jane K.; Khutoryanskiy, Vitaliy V.
Abstract: The role of mucoadhesion in the perception and sensory characterisation of food products is becoming more apparent. Traditionally, mucoadhesives are used to enhance drug permeability and retention at mucosal membranes in the body, by adherence to a mucosal membrane formed through various interactions between the mucoadhesive and proteins present in the mucosa. Many polysaccharides used in the food industry as thickeners, emulsifiers, stabilisers and fat replacers also have mucoadhesive properties, and are commonly used in the pharmaceutical industry in drug formulations. More recently, there has been an increasing interest in utilising these polysaccharides as mucoadhesives to modulate the organoleptic properties of food. This review reflects on the recent developments in mucoadhesion and the limited research into the impact of mucoadhesion when designing food formulations and modifying the organoleptic properties of food. It will also outline the areas of food science that could benefit from an understanding of mucoadhesion, mainly focusing on developing an understanding of how mucoadhesion may explain results found from sensory studies involving polysaccharides. Furthermore, possible negative impacts of mucoadhesion in foodstuff will be explored. An overview of methods for the measurement of mucoadhesion is also provided. An understanding of the mucoadhesive nature of polysaccharides may be useful to the food industry with regard to new product design. Graphical abstract: Highlights: Mucoadhesion is used in pharmaceutics to enhance drug retention at mucosal sites. The relevance of mucoadhesion to the food industry is a relatively novel concept. This review underlines the importance of mucoadhesion considering the pharmaceutical evidence and its role in sensory perception of food. It also covers methods to evaluate mucoadhesive materials.